Electronic government: perceptions of a process according to its own social stakeholders in the Lara state (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
With the new vision of the world, a series of aspects and philosophies are produced that are emerging to try to give answers to the organizations of the 21st century. This has generated a series of transformations in public organizations, specifically in the Venezuelan case, due to the constitutional and legal framework, where Electronic Government gains strength with the use of Information and Communication Technology (ICT), for economic development, social and political of the country. The purpose of this investigation was to reveal the nature, visions, characteristics and relationships that social actors attribute to the use of electronic government as a means to govern in Lara State. In this context, it was supported by the new organizational theories, the General Systems Theory, Cybernetic Theory and the New Economy. It was framed ontological, epistemological and methodological in the manifestations of the phenomenon and the qualitative nature was chosen, ascribing to the phenomenological - hermeneutical current. There were five (5) social actors selected from among Presidents, Directors and Managers of decentralized organizations in Lara State, the Lara State Governor's Office and the Andrés Eloy Blanco Municipality Mayor's Office in Lara State. The information collection technique was the interview in its semi-structured modality. The investigation allowed to generate a theoretical approximation in the implementation of the electronic government as a tool in the public management of the State of Lara.
Keywords: new economics; public management; electronic government; cybernetic theory; general systems theory